2023
DOI: 10.1007/978-3-031-26193-0_33
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Convolutional Network with Attention Mechanism for Bearing Remaining Useful Life Prediction

Abstract: Accurate prediction of the Remaining Useful Life (RUL) of rolling bearings is crucial in industrial production, yet existing models often struggle with limited generalization capabilities due to their inability to fully process all vibration signal patterns. We introduce a novel multi-input autoregressive model to address this challenge in RUL prediction for bearings. Our approach uniquely integrates vibration signals with previously predicted Health Indicator (HI) values, employing feature fusion to output cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…R is the lifetime of a run-tofailure instance. ris set to 125, according to [33][34][35]. Figure 10 shows the process of constructing the actual RUL of a run-to failure instance.…”
Section: Rul Definitionmentioning
confidence: 99%
“…R is the lifetime of a run-tofailure instance. ris set to 125, according to [33][34][35]. Figure 10 shows the process of constructing the actual RUL of a run-to failure instance.…”
Section: Rul Definitionmentioning
confidence: 99%
“…Attention networks utilize attention mechanisms to emphasize task-relevant information in deep learning networks through enhanced adaptive feature representation. To incorporate uncertainty quantification, Wang et al 58 used a Bayesian Kernel attention network for RUL prediction in bearings. The method produced more interpretable and trustworthy results in terms of the credible intervals for the RUL, along with the mean RUL prediction, thus providing a lot more information for decision-making when compared to existing methods of implementing attention networks that ignore uncertainty information and thus lead to overconfident RUL predictions.…”
Section: Uncertainty Quantification In Phmmentioning
confidence: 99%
“…Lim Meng Lip [11] et al cropped the surface profile images of machined parts and input them into CNN networks for tool wear prediction, and the results showed that the CNN model can meet the tool wear prediction requirements with an accuracy of 98.9 % accuracy. Although these methods have been successful in predicting tool wear, it is still challenging to fully reveal the effective features present in the monitored signals due to the defects in the network structure [12] .…”
Section: Introductionmentioning
confidence: 99%